Pengaruh Diskon Dan Suasana Toko Terhadap Impulse Buying Pada Department Store Mall Di Cirebon - Maulana Yusuf; Aditya Rizkian Kusuma; May Dedu (CV. AFDIFAL MAJU BERKAH, 2024)
This study iam to determine the effect influence of discount and store atmosphere towards impulse buying together. Methods in study is assosiative method. Because we know both of variabel or more with insidental sampling. The number of populations in this research is 75 people of Matahari department store Grage Mall Cirebon consumer’s. Analysis data is using validity, reliablity, classical assume, regression analysis, t test dan f test by using SPSS 23.0 version for windows. The result in this research shows that in partial discount is influence towards impulse buying(It can be seen from the value of tcount > ttable, namely 4.521 > 1.666. ), in partial store atmosphere is influence towards impulse buying (It can be seen from the value of tcount > ttable, namely 2382 > 1.666), and by simultaneous dicount and store atmosphere influence towards impulse buying (Fcount > Ftable is obtained, namely 18.141 > 3.12). The implications in this research is discount and storetmosphere both of partially and simultaneous is good enough. So that need to be maintaned but it would better if it enchance the discount and store atmosphere.